Positive electrode active material precursor and preparation method and application thereof
By designing a large-particle positive electrode active material precursor with loose internal and dense external structure and sintering at a lower temperature, the problem of high sintering temperature and mixed lithium nickel in the prior art is solved, and the high capacity and excellent cycling performance of a single crystal positive electrode material are achieved.
Patent Information
- Application Number
- CN202411784848.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-01
AI Technical Summary
When preparing single crystal positive electrode materials, the prior art faces the problem of high sintering temperature of large-particle precursors and mixed lithium nickel, resulting in reduced performance and high production costs.
A positive electrode active material precursor is provided, which includes a core and a shell covered on the surface of the core. The porosity of the core is greater than that of the shell. The average diameter of the core accounts for 30% to 70% of the total diameter of the precursor. The precursor is prepared by a co-precipitation reaction, and the sintering temperature is controlled at <950°C.
It significantly reduces the sintering temperature, saves production costs, reduces crystal structure defects such as lithium-nickel mixed discharge, and makes the single-crystal positive electrode material have excellent capacity and cycling performance.
Smart Images

Figure CN119735244A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a positive electrode active material precursor and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in 3C digital products, power tools, electric vehicles, energy storage and other fields due to their fast charging and discharging performance, environmental protection and recyclability. The positive electrode material is one of the important components of the battery, and the structure and performance of the positive electrode material play a vital role in the performance of the positive electrode material.
[0003] At present, positive electrode materials include single crystal particles and polycrystalline particles. Among them, polycrystalline particles are formed in micron-level agglomerates, and there are a large number of grain boundaries in the agglomerates. During the charge and discharge process of the battery, due to the anisotropic lattice changes, grain boundary cracking is prone to occur, resulting in the breakage of secondary particles, rapid increase of side reactions, increased impedance, and rapid decline in performance. Single crystal particles can reduce grain boundaries, reduce the occurrence of side reactions, and can also increase compaction density, thereby increasing energy density. Single crystal particles have high mechanical strength and structural stability, which helps to improve the cycle performance of the battery.
[0004] At present, most single-crystal cathode materials are prepared by sintering small and medium-sized particle precursors. For example, patent documents CN15924988A and CN115893522A mainly focus on the preparation of small and medium-sized particle precursors of 2 to 8 μm, and use small and medium-sized particle precursors of 2 to 8 μm to sinter into single-crystal morphology. However, there are few studies on large-particle precursors for preparing single-crystal cathode materials. This is because sintering into a single-crystal morphology usually requires increasing the sintering temperature. As the particle size of the precursor increases, the temperature required for sintering will only get higher and higher, and high-temperature sintering is prone to cause lithium-nickel mixing, and the production cost is high.
[0005] Therefore, how to provide a large-particle precursor that is conducive to the preparation of single-crystalline positive electrode materials is a technical problem that needs to be urgently solved in this field. Summary of the invention
[0006] The main purpose of the present invention is to provide a positive electrode active material precursor and a preparation method and application thereof, so as to solve the problems of high sintering temperature and lithium-nickel mixing in the preparation of single crystal positive electrode materials using existing large-particle precursors.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a positive electrode active material precursor, which includes a core and a shell coated on the surface of the core; wherein the porosity of the core is greater than the porosity of the shell; the average diameter of the core is d1, the D50 particle size of the positive electrode active material precursor is d, and satisfies: d1 / d×100%=30%~70%, and d is 10~18μm.
[0008] Furthermore, the inner core has a porosity of 16% to 20%; and / or, the inner core has macropores and mesopores, and the number of macropores accounts for more than 75%; preferably, the number of macropores accounts for 75% to 85%, and the number of mesopores accounts for 15% to 25%, wherein the pore size of the macropores is ≥50nm, and the pore size of the mesopores is 2nm≤<50nm.
[0009] Further, d1 is 4 to 10 μm; and / or the specific surface area of the positive electrode active material precursor is 3 to 7 m 2 / g.
[0010] Furthermore, the positive electrode active material precursor has a diffraction peak of the (001) crystal plane and a diffraction peak of the (101) crystal plane in the X-ray diffraction pattern, and the diffraction peak intensity I(001) of the (001) crystal plane and the diffraction peak intensity I(101) of the (101) crystal plane satisfy: I(101) / I(001)=0.50~0.65; the grain size D(101) is 8~15nm; the grain size D(001) is 16~23nm.
[0011] Furthermore, the chemical formula of the positive electrode active material precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, and 0.4≤x≤0.8, 0≤y≤0.4, 0≤z≤0.4.
[0012] The second aspect of the present invention provides a method for preparing a positive electrode active material precursor, comprising the following steps: preparing a reaction base liquid with pure water, a first alkali solution and a first complexing agent under an inert atmosphere; adding a metal salt solution, a second alkali solution and a second complexing agent to the reaction base liquid to form a reaction slurry, and causing the reaction slurry to undergo a coprecipitation reaction to obtain a positive electrode active material precursor; in the initial stage of the coprecipitation reaction, controlling the pH value of the reaction slurry to A1 and the ammonia content to B1, and when the product particle size D50 reaches 15-40% of the target particle size, controlling the pH value of the reaction slurry to A2 and the ammonia content to B2; satisfying: A1>A2.
[0013] Further, A1 is 11.30-12.50; and / or, B1 is 0.24-0.60 mol / L; and / or, A2 is 10.70-11.70; and / or, B2 is 0.24-0.60 mol / L; and / or, the volume of pure water added to the reactor is 30%-70% of the volume of the reactor; and / or, the temperature of the coprecipitation reaction is 55-75°C; when the reaction time is 0-1h, the stirring speed of the reaction slurry is controlled to be V1; when the reaction time is 1-5h, the stirring speed of the reaction slurry is controlled to be V2; when the reaction time is 5-8h, the stirring speed of the reaction slurry is controlled to be V3; satisfying: V1>V2>V3, preferably, V1 is 50-350r / min, V2 is 50-300r / min, and V3 is 50-200r / min.
[0014] Furthermore, the feed flow rate of the metal salt solution is 12 to 25 L / h; the concentration of the metal salt in the metal salt solution is 1 to 2.5 mol / L, and the metal salt includes at least one of nickel salt, cobalt salt, and manganese salt; the first alkali solution and the second alkali solution are sodium hydroxide solutions, wherein the concentration of sodium hydroxide is 4 to 12 mol / L; the first complexing agent and the second complexing agent are ammonia water, wherein the concentration of NH3 is 2 to 8 mol / L; and / or, the feed flow rate of the inert gas is 150 to 300 L / h.
[0015] Furthermore, after the coprecipitation reaction, the following steps are also included: aging the slurry after the coprecipitation reaction, then eluting and dehydrating the aged slurry with pure water at 60-85°C, and drying the dehydrated material in an oven at 80-140°C to a water content of <3000ppm.
[0016] The third aspect of the present invention provides a single crystal positive electrode material, which is obtained by sintering raw materials including a positive electrode active material precursor, wherein the positive electrode active material precursor includes the positive electrode active material precursor provided by the first aspect or the positive electrode active material precursor obtained by the preparation method provided by the second aspect, and the sintering temperature is less than 950°C.
[0017] The implementation of the present invention has at least the following beneficial effects:
[0018] The positive electrode active material precursor provided by the present invention limits the positive electrode active material precursor to have a loose structure inside and a dense structure outside, and limits the relationship between the average diameter of the inner core and the D50 particle size of the precursor. When the large-particle precursor is used to prepare a single-crystal positive electrode material, the sintering temperature can be significantly reduced, and the production cost can be saved. At the same time, the crystal structure defects such as lithium-nickel mixing can be reduced, so that the single-crystal positive electrode material has excellent capacity and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 This is a scanning electron microscope image of the positive electrode active material precursor in Example 1 of the present invention;
[0021] Figure 2 is a cross-sectional view of a positive electrode active material precursor in Example 1 of the present invention;
[0022] Figure 3 This is a scanning electron microscope image of the positive electrode active material precursor in Example 2 of the present invention;
[0023] Figure 4 is a cross-sectional view of a positive electrode active material precursor in Example 2 of the present invention;
[0024] Figure 5 This is a scanning electron microscope image of the positive electrode active material precursor in Comparative Example 1 of the present invention;
[0025] Figure 6 It is a cross-sectional view of the positive electrode active material precursor in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0027] As described in the background technology, the existing precursors for preparing single crystal positive electrode materials have the problems of high sintering temperature and lithium-nickel mixing. In order to solve the above technical problems, the present invention provides a positive electrode active material precursor, which includes a core and a shell coated on the surface of the core; wherein the porosity of the core is greater than the porosity of the shell; the average diameter of the core is d1, and the D50 particle size of the positive electrode active material precursor is d, which satisfies: d1 / d×100%=30%~70%, and d is 10~18μm.
[0028] The positive electrode active material precursor of the present invention can be mixed with a lithium source and converted into a positive electrode material through sintering treatment.
[0029] The porosity of the core of the positive active material precursor of the present invention is greater than the porosity of the shell, and the porosity can be obtained by profile testing. Specifically, the core porosity refers to the percentage of the pore area of the core to the total area of the core in the particle profile that constitutes the positive active material precursor; the shell porosity refers to the percentage of the pore area of the shell to the total area of the shell in the particle profile that constitutes the positive active material precursor. By limiting the porosity of the core of the positive active material precursor to be greater than the porosity of the shell, at this time, the core of the positive active material precursor is a loose porous structure, and the shell is denser than the core.
[0030] The average diameter d1 of the core refers to the average value of the core diameter in the particles constituting the positive electrode active material precursor, and the D50 particle size (d) of the positive electrode active material precursor refers to the particle size corresponding to when the cumulative volume percentage of the particles constituting the positive electrode active material precursor reaches 50%. By defining d1 / d×100%=30%~70%, and d is 10~18μm, the core diameter accounts for a large proportion in the positive electrode active material precursor with large particles.
[0031] d1 / d×100%=30%~70%, for example, 30%, 40%, 50%, 60%, 70% or a range consisting of any two thereof, d is 10~18μm, for example, 10μm, 12μm, 14μm, 16μm, 18μm or a range consisting of any two thereof.
[0032] In some embodiments, the specific surface area of the positive electrode active material precursor is 3 to 7 m 2 / g, for example 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g or a range consisting of any two thereof.
[0033] According to the research of the present invention, when the above-mentioned precursor is mixed with a lithium source for sintering, the outer shell contacts the lithium source first, the interior is loose and porous, and the inner core diameter accounts for a large proportion, and a single crystal morphology can be formed at a relatively low temperature, avoiding problems such as lithium-nickel mixing during high-temperature sintering, so that the single crystal positive electrode material has a higher capacity; in addition, the positive electrode material will inherit the structure and morphology of the above-mentioned precursor, and the loose and porous inner core diameter accounts for a large proportion, which is conducive to improving the diffusion of lithium ions. At the same time, the relatively dense outer shell is coated on the surface of the inner core, while ensuring sufficient infiltration of the electrolyte, avoiding excessive contact between the inner core and the electrolyte, improving the stability and cycle performance of the precursor, and making the single crystal positive electrode material have excellent cycle stability.
[0034] In some embodiments, the porosity of the inner core is 16% to 20%, for example, 16%, 17%, 18%, 19%, 20% or a range composed of any two thereof. Porosity refers to the percentage of the pore area of the inner core to the total area of the inner core in the cross section of the particles constituting the positive electrode active material precursor. The porosity can be obtained by cross-section testing. By limiting the porosity of the inner core, the present invention helps to ensure the structural stability of the positive electrode active material precursor while also improving the wettability of the electrolyte to it, thereby improving the electrochemical performance of the battery.
[0035] The inner core has macropores and mesopores, and is a hierarchical pore structure including mesopores and macropores, wherein the number of macropores accounts for more than 75%, and the number of macropores accounts for the proportion of the number of macropores in the number of all pores. In this way, the inner core forms a hierarchical pore structure with more macropores.
[0036] In some preferred embodiments, the number of macropores accounts for 75% to 85%, such as 75%, 80%, 85% or a range consisting of any two thereof, and the number of mesopores accounts for 15% to 25%, such as 15%, 20%, 25% or a range consisting of any two thereof, wherein the pore size of the macropores is ≥50nm, and the pore size of the mesopores is 2nm≤<50nm. Specifically, the pore size of the inner core can be measured by an pore size analyzer. Among them, the pore size of multiple macropores can be the same or different, and the pore size of multiple mesopores can be the same or different, and the present invention does not make too many restrictions here.
[0037] In some embodiments, the average diameter d1 of the kernel is 4 to 9 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or any two thereof. The average diameter refers to the average diameter size of the kernel in the cross section of the particles constituting the positive electrode active material precursor, which can be obtained by cross-section testing. By limiting the average diameter of the kernel, it is further ensured that the single crystal morphology can be formed at a lower temperature, avoiding problems such as lithium-nickel mixing during high-temperature sintering, and further improving the diffusion of lithium ions.
[0038] In some embodiments, the positive electrode active material precursor has a diffraction peak of the (001) crystal plane and a diffraction peak of the (101) crystal plane in the X-ray diffraction pattern, and the diffraction peak intensity I(001) of the (001) crystal plane and the diffraction peak intensity I(101) of the (101) crystal plane satisfy: I(101) / I(001)=0.50~0.65; the grain size D(101) is 8~15nm; the grain size D(001) is 16~23nm.
[0039] Wherein, D(001) is the grain size corresponding to the (001) crystal plane, and D(101) is the grain size corresponding to the (101) crystal plane. By controlling I(101) / I(001)=0.50-0.65, it is ensured that the positive electrode active material precursor has excellent crystallinity, thereby obtaining a single crystal positive electrode material with good crystallinity. In addition, by limiting the specific values of D(001) and D(101), the interplanar spacing of the positive electrode active material is large, which is conducive to the diffusion of lithium ions.
[0040] I(101) / I(001)=0.50-0.65, for example, 0.5, 0.55, 0.6, 0.65 or a range consisting of any two thereof; the grain size D(101) is 8-15nm, for example, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm or a range consisting of any two thereof; the grain size D(001) is 16-23nm, for example, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm or a range consisting of any two thereof.
[0041] In some embodiments, the chemical formula of the positive electrode active material precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, and 0.4≤x≤0.8, 0≤y≤0.4, 0≤z≤0.4. That is to say, the positive electrode active material precursor can be a nickel hydroxide precursor, a nickel cobalt hydroxide precursor, or a nickel cobalt manganese ternary hydroxide precursor, and the present invention does not make too many restrictions here.
[0042] The positive electrode active material precursor of the present invention can be a secondary particle formed by agglomeration of primary particles, which includes a plurality of secondary particles, and the secondary particles can be a spherical or quasi-spherical structure with a low sphericity "grape-like". In some embodiments, the primary particles of the inner core are intertwined and randomly arranged, and the primary particles of the outer shell are lath-shaped and stacked tightly.
[0043] The second aspect of the present invention provides a method for preparing a positive electrode active material precursor, comprising the following steps: preparing a reaction base liquid with pure water, a first alkali solution and a first complexing agent under an inert atmosphere; adding a metal salt solution, a second alkali solution and a second complexing agent to the reaction base liquid to form a reaction slurry, and causing the reaction slurry to undergo a coprecipitation reaction to obtain a positive electrode active material precursor; wherein, in the initial stage of the coprecipitation reaction, the pH value of the reaction slurry is controlled to be A1, and the ammonia content is controlled to be B1, and when the product particle size D50 reaches 15-40% of the target particle size, the pH value of the reaction slurry is controlled to be A2, and the ammonia content is controlled to be B2; satisfying: A1>A2, B1>B2.
[0044] In the present invention, a metal salt solution, an alkali solution and a complexing agent undergo a coprecipitation reaction in a reaction kettle, wherein the alkali solution serves as a precipitating agent and ammonia water serves as a complexing agent. The coprecipitation reaction includes a nucleation stage and a growth stage.
[0045] The crystallization process of crystalline materials is divided into two stages: nucleation and nuclear growth. Specifically, a crystal nucleus is first formed in the reaction slurry, and then a positive electrode active material precursor with a specific size grows on the basis of the crystal nucleus. The process of forming the crystal nucleus is the nucleation stage, and the process of forming a positive electrode active material precursor with a specific size is the nuclear growth stage.
[0046] In the specific implementation process of the present invention, water, alkali solution and complexing agent are added to the reactor in advance as the reaction base liquid, so that the pH value and ammonia value can meet the requirements of the nucleation stage, effectively ensure the high repeatability of the preparation method, and avoid the influence of fluctuations in the synthesis conditions in the nucleation stage. For example, pure water is first added to the reactor, and then alkali solution and ammonia water are added to adjust the pH value to A1 and the ammonia content to B1.
[0047] The present invention has been found through research that the nucleation is significantly affected by regulating the amount of pure water added and the pH and ammonia content of the reaction process. In particular, the present invention can effectively control the degree of agglomeration of primary particles by limiting the conditions of high pH and high ammonia content, thereby satisfying the relationship of d1 / d×100%=30% to 70%, and d is 10 to 18 μm. Specifically, when A1>A2, B1>B2 are satisfied, that is, nucleation occurs under relatively high pH and relatively high ammonia content conditions, and growth occurs under relatively low pH and relatively low ammonia content conditions, the above nucleation conditions and growth conditions can effectively control the degree of agglomeration of primary particles.
[0048] In the specific implementation process of the present invention, the pH value of the reaction slurry can be regulated by controlling the feed flow rate of the alkali solution, and the ammonia value of the reaction slurry can be regulated by controlling the feed flow rate of the complexing agent.
[0049] In some preferred embodiments, A1 is 11.30-12.50; and / or, B1 is 0.24-0.60 mol / L, for example, 0.24 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L or a range consisting of any two thereof; and / or, A2 is 10.70-11.70; and / or, B2 is 0.24-0.60 mol / L, for example, 0.24 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L or a range consisting of any two thereof.
[0050] In some embodiments, the volume of pure water added to the reactor accounts for 30% to 70%, that is, the volume of pure water added to the reactor is 30% to 70% of the volume of the reactor, such as 30%, 40%, 50%, 60%, 70% or any two of them. In some preferred embodiments, when the reactor is a 150L reactor, the volume of pure water added to the reactor is 45 to 105L, such as 45L, 50L, 55L, 60L, 70L, 80L, 90L, 100L, 105L or any two of them. In this way, nucleation at a relatively low pure water content can effectively control the degree of agglomeration of primary particles, which is helpful to obtain a precursor that meets the above requirements.
[0051] In some embodiments, the temperature of the coprecipitation reaction is 55-75° C. By limiting the temperature, it is helpful to form a precursor with the above-mentioned morphological characteristics.
[0052] In some embodiments, when the reaction time is 0 to 1 hour, the stirring speed of the reaction slurry is controlled to be V1; when the reaction time is 1 to 5 hours, the stirring speed of the reaction slurry is controlled to be V2; when the reaction time is 5 to 8 hours, the stirring speed of the reaction slurry is controlled to be V3; and V1>V2>V3 is satisfied. In this way, by limiting the nucleation stage to be carried out under relatively high rotation speed conditions, a core with the above characteristics is formed, and the dispersion of the crystal nucleus can be improved and agglomeration can be reduced, while the rotation speed is reduced in the growth stage to avoid the growth of particles due to friction, collision, cracking or even fragmentation.
[0053] The present invention does not limit the specific value range of V1, V2, and V3, as long as V1>V2>V3 is satisfied. In some preferred embodiments, V1 is 50-350 r / min, V2 is 50-300 r / min, and V3 is 50-200 r / min.
[0054] The present invention does not limit the physical parameters of the metal salt solution, alkali solution and complexing agent, and can be adjusted according to actual production needs. For example, in some embodiments, the feed flow rate of the metal salt solution is 12 to 25 L / h; the concentration of the metal salt in the metal salt solution is 1 to 2.5 mol / L, and the metal salt includes at least one of nickel salt, cobalt salt and manganese salt; the first alkali solution and the second alkali solution are sodium hydroxide solution, wherein the concentration of sodium hydroxide is 4 to 12 mol / L; the first complexing agent and the second complexing agent are ammonia water, wherein the concentration of NH3 is 2 to 8 mol / L; the feed flow rate of the inert gas is 150 to 300 L / h.
[0055] The present invention finely controls the parameters of the reaction system, such as pH value, ammonia value, temperature, flow rate, etc., which is not only beneficial to the generation and growth of crystal nuclei, but also beneficial to improving the repeatability of the preparation method.
[0056] In order to obtain the positive electrode active material precursor, a post-treatment step is also included after the coprecipitation reaction, and the post-treatment includes aging treatment, washing treatment, drying treatment, etc. Specifically, when the material particle size D50 of the reaction slurry in the reactor reaches the target particle size, the feeding is stopped and the synthesis is completed; the reaction slurry in the reactor is collected, and post-treatment processes such as aging treatment, washing treatment, drying treatment, etc. are performed to obtain the positive electrode active material precursor.
[0057] The slurry after the coprecipitation reaction is aged, and then the aged slurry is rinsed and dehydrated with pure water at 60-85° C., and the dehydrated material is dried in an oven at 80-140° C. to a water content of less than 3000 ppm.
[0058] In addition, post-processing also includes screening and demagnetization, that is, after drying, the dried material is subjected to screening and demagnetization in sequence to finally obtain a positive electrode active material precursor. Screening can be performed using a 325-mesh vibrating screen.
[0059] The second aspect of the present invention provides a single crystal positive electrode material, which is obtained by sintering raw materials including a positive electrode active material precursor, wherein the positive electrode active material precursor includes the positive electrode active material precursor provided by the first aspect or the positive electrode active material precursor obtained by the preparation method provided by the second aspect, and the sintering temperature is less than 950°C.
[0060] Specifically, the positive electrode active material precursor can be directly subjected to lithiation sintering treatment to obtain a single crystal positive electrode material, or the positive electrode active material precursor can be mixed with other doping elements and / or coating elements and then subjected to lithiation sintering treatment to obtain a single crystal positive electrode material.
[0061] Since the positive electrode active material precursor having a specific morphology and satisfying specific parameters is used for sintering, a single crystal positive electrode material can be obtained at a relatively low sintering temperature (<950° C.), while taking into account high capacity and excellent cycle performance.
[0062] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0063] Example 1
[0064] The preparation of the positive electrode active material of this embodiment includes the following steps:
[0065] S1, nickel sulfate, cobalt sulfate, manganese sulfate and water are mixed according to the target molar ratio to obtain a metal salt solution with a total metal ion concentration of 2.2 mol / L, and a sodium hydroxide solution with a concentration of 5 mol / L and an ammonia solution with a concentration of 5 mol / L are prepared;
[0066] S2. Add pure water, sodium hydroxide solution and ammonia water to a 150L reactor, and introduce nitrogen for protection to form a reaction bottom liquid; wherein, the amount of pure water added is 50L, the pH value of the reaction bottom liquid is adjusted to 11.50, the ammonia content is 0.53mol / L, the reactor temperature is 70°C, and the stirring speed of the reactor is 350r / min;
[0067] S3, passing the metal salt solution, sodium hydroxide solution and ammonia solution into the reaction bottom liquid for coprecipitation reaction, and continuously passing nitrogen protection, controlling the pH value to 11.50, the ammonia content to 0.53 mol / L, and the reactor temperature to 70°C. When D50 is 4.5 μm, the pH is reduced to 11.00 by regulating the feed flow rate of the sodium hydroxide solution, and it is reduced to the desired level in 70s. The ammonia content is 0.35 mol / L by regulating the feed flow rate of the ammonia solution, and the reactor temperature is 70°C. The reactor slurry volume is maintained at a certain volume by clearing; when the particle size D50 grows to 14.0 μm, the feeding is stopped; wherein, when the reaction time is 5 h, the rotation speed is adjusted to 200 r / min; when the reaction time is 8 h, the rotation speed is adjusted to 150 r / min, and the feed flow rate of the metal salt solution is 12 L / h; the flow rate of the nitrogen is 120 L / h;
[0068] S4. Maintain the temperature of the reactor at 70°C and maintain the speed at shutdown for 2 hours; rinse the aged slurry with 85°C pure water and dehydrate it, dry the dehydrated washed material in an oven at 130°C to H2O < 3000ppm, then cool it to room temperature, and sieve the dried material with a 325-mesh vibrating screen. After iron removal, Ni with a D50 of 14.0μm is obtained. 0.65 Co 0.16 Mn 0.19 (OH)2 cathode active material precursor (such as Figure 1 and Figure 2 shown).
[0069] Example 2
[0070] The preparation of the positive electrode active material of this embodiment includes the following steps:
[0071] S1, nickel sulfate, cobalt sulfate, manganese sulfate and water are mixed according to the target molar ratio to obtain a metal salt solution with a total metal ion concentration of 2.2 mol / L, and a sodium hydroxide solution with a concentration of 5 mol / L and an ammonia solution with a concentration of 5 mol / L are prepared;
[0072] S2. Add pure water, sodium hydroxide solution and ammonia water to a 150L reactor, and introduce nitrogen for protection to form a reaction bottom liquid; wherein, the amount of pure water added is 50L, the pH value of the reaction bottom liquid is adjusted to 11.90, the ammonia content is 0.32mol / L, the reactor temperature is 75°C, and the stirring speed of the reactor is 350r / min;
[0073] S3, passing the metal salt solution, sodium hydroxide solution and ammonia solution into the reaction bottom liquid for coprecipitation reaction, and continuously passing nitrogen protection, controlling the pH at 11.90, and the ammonia content reaching 0.32 mol / L, when D50 grows to 4.5 μm, the pH is reduced to 11.30 by regulating the feed flow rate of the sodium hydroxide solution, and it drops to the right position in 70s, and the ammonia content is reduced to 0.3 mol / L by regulating the feed flow rate of the ammonia solution, the reactor temperature is 75°C, and the reactor slurry volume is maintained at a constant volume by clearing; when the reaction time is 1h, the speed is adjusted to 200r / min; when the reaction time is 8h, the speed is adjusted to 150r / min, and when the particle size D50 grows to 14.0μm, the feeding is stopped; wherein, the feed flow rate of the metal salt solution is 12L / h; the flow rate of the nitrogen is 120L / h;
[0074] S4. Maintain the reactor temperature at 75°C and maintain the speed at shutdown for 1 hour; rinse the aged slurry with 85°C pure water and dehydrate it, dry the dehydrated washed material in an oven at 130°C to H2O < 3000ppm, then cool it to room temperature, and sieve the dried material with a 325-mesh vibrating screen. After iron removal, Ni with a D50 of 14.0μm is obtained. 0.65 Co 0.16 Mn 0.19 (OH)2 cathode active material precursor (such as Figure 3 and Figure 4 shown).
[0075] Example 3
[0076] Compared with Example 1, in S2, the reactor temperature is 65° C., the ammonia content is controlled to be 0.42 mol / L, and other conditions remain unchanged.
[0077] Comparative Example 1
[0078] The preparation of the positive electrode active material precursor of this comparative example includes the following steps:
[0079] S1. Mix nickel sulfate, cobalt sulfate and manganese sulfate with water according to a target molar ratio to obtain a metal salt solution with a total metal ion concentration of 2 to 2.3 mol / L, and prepare a sodium hydroxide solution with a concentration of 6 to 10 mol / L and an ammonia solution with a concentration of 4 to 6 mol / L;
[0080] S2. Add pure water, sodium hydroxide solution and ammonia water to a 150L reactor, and introduce nitrogen for protection to form a reaction bottom liquid; wherein, the amount of pure water added is 120L, the pH value of the reaction bottom liquid is adjusted to 11.50, the ammonia content is 0.2mol / L, the reactor temperature is 65°C, and the stirring speed of the reactor is 350r / min;
[0081] S3, introducing metal salt solution, sodium hydroxide solution and ammonia water into the reaction bottom liquid for coprecipitation reaction, and continuously introducing nitrogen protection, controlling the pH value to be 11.70, the ammonia content to be 0.3 mol / L, the reactor temperature to be 65°C, and the reactor slurry volume to be maintained at a certain volume by clearing; when the reaction time is 1h, adjusting the speed to 200r / min; when the reaction time is 8h, adjusting the speed to 150r / min, and stopping feeding when the particle size D50 grows to 14.0μm; wherein, the feed flow rate of the metal salt solution is 12L / h; the feed flow rate of the nitrogen is 120L / h;
[0082] S4. Maintain the temperature of the reactor at 65°C and maintain the speed at shutdown for 1 hour; rinse the aged slurry with 85°C pure water and dehydrate it, dry the dehydrated washed material in an oven at 130°C to H2O < 3000ppm, then cool it to room temperature, and sieve the dried material with a 325-mesh vibrating screen. After iron removal, Ni with a D50 of 14.0μm is obtained. 0.70 Co 0.10 Mn 0.20 (OH)2 cathode active material precursor (such as Figure 5 and Figure 6 shown).
[0083] Comparative Example 2
[0084] Compared with Example 1, in S2, the stirring speed of the reactor is 300 r / min, the ammonia content is controlled to be 0.7 mol / L, and other conditions remain unchanged.
[0085] Test example
[0086] 1. Performance of positive electrode active material precursor
[0087] (1) D50 particle size
[0088] The D50 was measured using a Malvern laser particle size analyzer (MS-3000).
[0089] (2) Pore size distribution and porosity test in the core
[0090] Through SEM observation, Figures 1 to 6 As shown, the amount of nitrogen adsorbed on the material surface is measured to determine the core porosity and pore size distribution.
[0091] (3) Average kernel diameter test
[0092] The average diameter of the core was measured by SEM observation and Nano Measurer 1.2. 200 particles were selected from the SEM image, and their diameters were measured and their average values were calculated to obtain the average core diameter.
[0093] (4) Specific surface area test
[0094] The test was carried out using a fully automatic nitrogen adsorption specific surface area tester.
[0095] (5) Grain size test
[0096] X-ray diffraction (XRD) was used to measure the width of the diffraction peak, and the grain size was calculated based on the width of the diffraction peak.
[0097] 2. Performance of single crystal cathode materials
[0098] The precursors of the embodiment and the comparative example were mixed according to the element molar ratio (Ni+Co+Mn):Li=1:1.05, heated to a certain temperature in a muffle furnace at a heating rate of 5°C / min, calcined for 14 hours, and cooled to obtain a single crystal positive electrode material.
[0099] The above-mentioned single crystal positive electrode material, acetylene black (AB), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone (NMP) is used as a solvent. The mixture is placed in a beaker and stirred at a speed of 800r / min for 2h to obtain a slurry; the slurry is coated on a current collector aluminum foil using an automatic coating machine, placed flat on tempered glass and transferred to a vacuum drying oven at 85°C for drying for 4h, punched into a pole piece with a diameter of 12mm, and then dried at 105°C in a vacuum drying oven for 4h, placed in a glove box with an argon atmosphere with a water content and an oxygen content both lower than 0.1ppm for 4h to reduce the moisture adsorbed by the pole piece during the transfer process, rolled the metallic lithium into a thin sheet, and punched into a 14mm round lithium sheet as a negative electrode, and assembled into a button battery in the glove box.
[0100] After aging the assembled battery for 12 hours, the first charge and discharge capacity test was performed. The test conditions were: charge to 4V at 0.2C, stand for 1 minute, and then discharge to 2.2V at 0.2C. The charge and discharge curves were obtained, and the first discharge specific capacity D0 from 2.2 to 4V was recorded respectively.
[0101] The battery was charged and discharged at 25°C using a battery charge and discharge tester. The battery was charged to 4V at 0.1C constant current, and then discharged to 2.2V at 0.1C constant current after standing for 1 minute. This cycle was repeated for 5 cycles. After standing for 1 minute, the battery was charged to 4V at 1C constant current. After standing for 1 minute, the battery was discharged to 2.2V at 1C constant current. This cycle was repeated for 100 cycles. The discharge capacity Q1 at the first cycle under 1C conditions and the discharge capacity Q at the 100th cycle under 1C conditions were determined. 100 , calculate the capacity retention rate after 100 cycles according to the following formula:
[0102] Capacity retention rate Q = Q 100 / Q1×100%.
[0103] The test results are shown in Table 1 and Table 2.
[0104] Table 1
[0105]
[0106]
[0107] In Table 1, d represents D50 of the positive electrode active material precursor, and d1 represents the average diameter of the core.
[0108] Table 2
[0109]
[0110] according to Figures 1 to 4 It can be seen that the positive electrode active material precursor of the embodiment of the present invention is a secondary particle formed by agglomeration of primary particles, which includes a plurality of secondary particles, and the secondary particles are spherical or quasi-spherical structures with low sphericity "grape-like". Among them, the primary particles of the inner core are intertwined and randomly arranged, and the primary particles of the outer shell are lath-shaped and stacked tightly.
[0111] According to Table 1 and Table 2, the present invention can obtain a large-particle positive electrode active material precursor (D50 is 10-18 μm) with a loose and porous core and a dense shell by regulating the amount of pure water added and the pH and ammonia content of the reaction process, and the number of macropores in the core accounts for more than 75%, satisfying d1 / d×100%=30%-70%. When the precursor of the present invention is mixed with a lithium source for sintering, a single crystal morphology can be formed at a lower temperature, avoiding problems such as lithium-nickel mixing during high-temperature sintering, so that the single crystal positive electrode material has a higher capacity; in addition, the positive electrode material will inherit the structure and morphology of the above-mentioned precursor, so that the single crystal positive electrode material has excellent cycle performance.
[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode active material precursor, characterized in that: The positive electrode active material precursor includes a core and a shell coated on the surface of the core; wherein the porosity of the core is greater than the porosity of the shell; the average diameter of the core is d1, the D50 particle size of the positive electrode active material precursor is d, and satisfies: d1 / d×100%=30%~70%, and d is 10~18μm.
2. The positive electrode active material precursor according to claim 1, characterized in that: The porosity of the inner core is 16% to 20%; and / or the inner core has macropores and mesopores, and the number of the macropores accounts for more than 75%; preferably, the number of the macropores accounts for 75% to 85%, and the number of the mesopores accounts for 15% to 25%, wherein the pore size of the macropores is ≥50nm, and the pore size of the mesopores is 2nm≤<50nm.
3. The positive electrode active material precursor according to claim 1, characterized in that: The d1 is 4 to 10 μm; and / or the specific surface area of the positive electrode active material precursor is 3 to 7 m 2 / g.
4. The positive electrode active material precursor according to claim 1, characterized in that: The positive electrode active material precursor has a diffraction peak of the (001) crystal plane and a diffraction peak of the (101) crystal plane in an X-ray diffraction spectrum, and the diffraction peak intensity I(001) of the (001) crystal plane and the diffraction peak intensity I(101) of the (101) crystal plane satisfy: I(101) / I(001)=0.50-0.65; the grain size D(101) is 8-15 nm; The grain size D(001) is 16-23 nm.
5. The positive electrode active material precursor according to claim 1, characterized in that: The chemical formula of the positive electrode active material precursor includes Ni x Co y Mn z (OH)2, wherein x+y+z=1, and 0.4≤x≤0.8, 0≤y≤0.4, 0≤z≤0.
4.
6. A method for preparing a positive electrode active material precursor according to any one of claims 1 to 5, characterized in that: The following steps are involved: Under an inert atmosphere, preparing a reaction base liquid with pure water, a first alkali solution and a first complexing agent; Adding a metal salt solution, a second alkali solution and a second complexing agent to the reaction base liquid to form a reaction slurry, and causing the reaction slurry to undergo a coprecipitation reaction to obtain a positive electrode active material precursor; wherein, in the initial stage of the coprecipitation reaction, the pH value of the reaction slurry is controlled to be A1, and the ammonia content is controlled to be B1; when the product particle size D50 reaches 15% to 40% of the target particle size, the pH value of the reaction slurry is controlled to be A2, and the ammonia content is controlled to be B2; Satisfies: A1>A2, B1>B2.
7. The preparation method according to claim 6, characterized in that: A1 is 11.30-12.50; and / or, B1 is 0.24-0.60 mol / L; and / or, A2 is 10.70-11.70; and / or, B2 is 0.24-0.60 mol / L; and / or, the volume of pure water added to the reactor is 30%-70% of the volume of the reactor; and / or, the temperature of the coprecipitation reaction is 55-75°C; when the reaction time is 0-1h, the stirring speed of the reaction slurry is controlled to be V1; when the reaction time is 1-5h, the stirring speed of the reaction slurry is controlled to be V2; when the reaction time is 5-8h, the stirring speed of the reaction slurry is controlled to be V3; satisfying: V1>V2>V3, preferably, V1 is 50-350r / min, V2 is 50-300r / min, and V3 is 50-200r / min.
8. The preparation method according to claim 6, characterized in that: The feed flow rate of the metal salt solution is 12 to 25 L / h; the concentration of the metal salt in the metal salt solution is 1 to 2.5 mol / L, and the metal salt includes at least one of a nickel salt, a cobalt salt, and a manganese salt; the first alkali solution and the second alkali solution are sodium hydroxide solutions, wherein the concentration of sodium hydroxide is 4 to 12 mol / L; the first complexing agent and the second complexing agent are ammonia water, wherein the concentration of NH3 is 2 to 8 mol / L; and / or the feed flow rate of the inert gas is 150 to 300 L / h.
9. The preparation method according to claim 6, characterized in that: After the coprecipitation reaction, the method further comprises the following steps: aging the slurry after the coprecipitation reaction, then rinsing and dehydrating the aged slurry with pure water at 60-85°C, and drying the dehydrated material in an oven at 80-140°C to a water content of less than 3000ppm.
10. A single crystal positive electrode material, characterized in that: The positive electrode active material precursor is prepared by sintering raw materials including a positive electrode active material precursor, wherein the positive electrode active material precursor includes the positive electrode active material precursor described in any one of claims 1 to 5 or the positive electrode active material precursor prepared by the preparation method described in any one of claims 6 to 9, and the sintering temperature is less than 950°C.
Citation Information
Patent Citations
Hollow ternary positive electrode material, precursor and preparation method of hollow ternary positive electrode material
CN115893522A
Cited By
Composite positive electrode material precursor and preparation method thereof, positive electrode active material and battery
CN121361846A